The Development of the Eye in the Binni Barbus Sharpeyii Gunther - N.A. Al-Bakri (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The embryonic development of the eye in Barbuc sharpyeii has been investigated. The first sign of the eye development represented by evagination on both sides of the forebrain anlage 1n embryo at (27) hrs. after fertilization. The primordium of differentiated to optic vesicle in embryo at (3 1) hrs. after fertilization and then part of the optic vesicle which in front the ectoderm investigation, the optic cup will formed in embryo at (40) after fertilization. The optic cup has a double layers wall, the internal laver represented the eye reticulum while the outer layer represented the pigmented layer. During the larva age of (72) hrs. after fertilization of the cornea and sclera primordiums appeared in larva age (96) hr. after fertilization of the reticular laver differentiate to the inner nuclear layer, outer nuclear layer, Inner plexiform layer, internal limiting membrane. In larva at (216 & 384) hr. after fertilization the reticular layer differentiate to the external limited membrane, Ganglion cell layer, Internal plexiform layer, outer plexiform layer, outer nuclear layer, cones and rods Zone. At the same age, the optic nerve which connects with the mesencephalon roof appears and the iris and ciliary body appear while the ‣ optic cup development completed. On the other hand, the first sign of the eye lens appears as a lens age (38) hrs, after fertilization placode from the ectoderm in front of the optic vesicle in embryo at embryo at (40) hrs, after fertilization, eye lens differentiate then it changes to lens vesicle in spherical shape complete lens in larva at (72) hrs, after fertilization, and it lakes cell attached with lens fbers. The anterior in larva at (96) hrs. after fertilization. surfaces of the lens appear as single row of epithelial. After the completion of the lens differentiation and situated in between the edges of the optice cup, and appearanee of complete sclera, iris, and ciliary body of the eye. The eye development completed and the eye becomes similar to that in an adult fish.